Invasive plants reduce functional feeding diversity and trophic interactions of insect herbivores on a remote tropical island - Maia R. Supple; Jaemin Lee (PLoS ONE, 2026)
Invasive plants are a driver of global insect decline, yet their impacts on trophic interactions in insular tropical island ecosystems remain poorly understood. We investigated patterns of insect herbivory in the lowland rainforest of Moʻorea, French Polynesia—a remote tropical island in the South Pacific—on a total of twelve species of native, naturalized (introduced, non-invasive), and invasive host plants common in the forest. Using the functional feeding group–damage type system—a functional approach commonly applied in paleoecological studies that investigates traces of insect and fungal herbivory—we quantified the diversity and abundance of herbivory traces on fresh leaf litter and constructed weighted bipartite networks to assess community structure. Our results show a significantly reduced trophic interaction on invasive plants, which experienced substantially lower functional diversity and intensity of insect herbivory across all functional groups (e.g., stylophytic feeding, galling, margin feeding) compared to native and naturalized ones. Network analysis confirms that invasive plants held peripheral, weakly connected positions, whereas native and naturalized plants had central roles in integrating the trophic interactions. The high connectivity of naturalized plants in the network analysis, as well as comparable herbivory diversity and intensity to native species, suggest their successful assimilation into the local community, implying that susceptibility to herbivory may suppress the population expansion and invasion of some introduced plants. The prevalence of rare and specialized interactions and the power-law distribution of the number of host plants each damage type occurs on, observed in our study, mirrored the global patterns of host plant usage by insect herbivores—dominated by rare and specialized interactions—further suggesting the functional feeding group–damage type system as a robust and efficient tool for comparative insect herbivory investigations.